ANALISIS TEMPERATUR BLDC MOTOR ROTOMAX 150 CC DENGAN PARAMETER POWER, RPM, DAN FORCE - Aria Bima; Erwan Eko Prasetiyo; M. Faiz Alfatih (Sekolah Tinggi Teknologi Kedirgantaraan, 2022)
The use of BLDC motors in UAVs today is increasing, this is because the efficiency value is relatively good when compared to other types of motors. The advantages of the BLDC motor are that it is easy to maintain, the sound is relatively not too noisy and is environmentally friendly because it does not emit residue. However, over time the BLDC operates, the temperature of the BLDC motor will increase, so a temperature analysis is needed to ensure that the BLDC is still within the safe limits for use. With this analysis, it is hoped that it will increase the lifespan of the BLDC and avoid the use of an overloaded BLDC. In this study, several tests were carried out to observe the BLDC temperature for variations in power, RPM, and the resulting force. This research was conducted experimentally by arranging measuring devices in such a way as to determine the performance of the BLDC. For validation purposes, data collection is carried out 2 times, so that to get a conclusion, it can be done by looking for the average. The results of the study show that the higher the value of power, RPM, and force, the temperature of the BLDC will increase. Characteristics of the improvement of each of each parameter is linear. From the test results, the lowest temperature was reached at 36.65 °C at a power condition of 14.75 W, RPM